A method for approximate on‐farm estimation of herbage mass by using two assessments per pasture. (4th November 2015) - Nakagami, K.
Abstract: Appropriate pasture management requires implementation of methods that reduce the time and labour required for assessing herbage mass. In this study, Monte Carlo simulations and a field study were used to evaluate a simple method for estimating herbage mass based on the corrected average of the single highest and lowest mass values in a pasture. The necessary correction factor for the method was objectively derived using a single nonlinear equation based on the scaled difference between the highest and lowest herbage mass regardless of the mean and variance of mass and pasture size. The accuracy of estimation using this method is acceptable for on‐farm use: more than 90% of the estimates had error rates below 20% of the true value when the plot size assessed was larger than 64 m 2 in the simulation study; in the field experiment, approximately half of the estimates had error rates below 20% of the observed mean of random samples ( R 2  = 0·71). The advantages of the proposed method are that it requires only two assessments per pasture and that selection of assessment plots is straightforward. This method has potential for obtaining approximate on‐farm estimates of herbage mass that could help improve pasture management.